2018
DOI: 10.11124/jbisrir-2017-003584
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to activity monitoring devices or smartphone applications for improving physical activity in adults with cardiovascular disease: a systematic review protocol

Abstract: The question of this review is: what is the adherence to the use of activity monitoring devices or applications to improve physical activity in adults with cardiovascular disease?Specifically, the review objectives are.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…This systematic review was undertaken using a protocol peer reviewed by JBI 24 and registered with PROSPERO (CRD: 42018094781). It follows the preferred reporting items for systematic review and meta-analyses: the PRISMA Statement (Supplementary Material file I online).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This systematic review was undertaken using a protocol peer reviewed by JBI 24 and registered with PROSPERO (CRD: 42018094781). It follows the preferred reporting items for systematic review and meta-analyses: the PRISMA Statement (Supplementary Material file I online).…”
Section: Methodsmentioning
confidence: 99%
“…This systematic review was undertaken using a protocol peer reviewed by JBI 27 and registered with PROSPERO. 28…”
Section: Protocol and Registrationmentioning
confidence: 99%
“…For example, they do not obtain results from the older people, they do not focus exclusively on PA applications, and they only include randomised controlled clinical studies. [24][25][26] Therefore, this scoping review will be the first to map specific factors of the older population relating to the adoption or adherence of PA mobile applications across a range of study types, based on existing literature.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…With the popularity and widespread use of the Internet, providing exercise interventions, nutritional support, and psychological interventions for patients through smartphone apps has become possible. The results of a large number of global studies have shown that interventions for patients through smartphone apps, online platforms, and online video calls can effectively improve the quality of life and physical function of breast cancer patients during the recovery period following treatment ( Gokal et al, 2016 ; Kourbelis et al, 2018 ; Hayes et al, 2019 ). These results verify the effectiveness, applicability, and acceptability of smartphone apps.…”
Section: Introductionmentioning
confidence: 99%